Enhancing Roundabout Efficiency Through Autonomous Vehicle Coordination - Antonya, Csaba; Iclodean, Calin; Roșu, Ioana-Alexandra (MDPI AG, 2025)
The paper discusses the potential for autonomous vehicles to improve traffic flow on roundabouts, suggesting that their ability to slow down strategically can enhance traffic and reduce pollution on both main and yielding roads. A traffic simulator for a roundabout was developed for a busy intersection of a new city neighborhood. We consider that some of the cars are self-driving, and they are fully aware of the traffic scenario. By optimizing their speed and timing their speed reduction, these vehicles can help maintain a balance between the number and time of crossing vehicles on both the main and yielding roads. This study evaluates the effectiveness of the intervention, demonstrating that autonomous vehicles can significantly improve roundabout efficiency, reducing congestion and pollution. The application of genetic algorithms is highlighted as an effective optimization method to find the right autonomous vehicle’s timing and speed reduction ratio combination on the main road to enhance traffic efficiency.
Keywords: autonomous vehicle; traffic; genetic algorithm; traffic simulator; optimization; roundabout